Cost of illness coronavirus disease 2019 (covid-19) with comorbidities in a hospital in west java - Alfi Nurul Islamiyah; Oskar Skarayadi; Nur Hafidah Turrahmat; Siti Susiani (Science Midwifery, 2023)
Epidemiological evidence has suggested that individuals with chronic disease may have a 10-fold risk of developing severe COVID-19 disease compared to individuals without comorbidities. The analysis that estimates the cost of treating COVID-19 patients is still very limited, especially in Indonesia. Thus, in this study, disease costs will be carried out to analyze the costs of clinical management of COVID-19 in patients with comorbidities during hospitalization. This study is a descriptive study using the economy evaluation method, in which the burden of the economy of the COVID-19 disease is included in the direct costs. Sampling was carried out with a purposive sampling method in inpatient COVID-19 patients who had comorbidities at a hospital in West Java during the second wave of COVID-19 in Indonesia (June, July, and August 2021). Ninety-six patients were diagnosed with COVID-19 with comorbid CAP and comorbid Type 2 DM, whose cost data were evaluated with the cost of illness. The total cost of COVID-19 patients with comorbid CAP is Rp. 1,773,944,688 with an average cost of Rp. 25,342,067 ± 10,550,734, and comorbid type 2 diabetes is Rp. 782,391,792 with an average cost of Rp. 30,091,992 ± 14,773,533. The average length of stay for COVID-19 patients with comorbid CAP was 10.1 ± 3.6 days, and comorbid type 2 DM was 11.3 ± 4.5 days. These results indicate that COVID-19 with comorbidities provides a considerable burden on patients, increases the length of treatment for patients, and is quite expensive.